La Granja (New York : Scholastic, 2013)
Introduces the different types of farms, farm animals, crops, farm equipment, the kinds of work done on farms, and related topics.
"Libro digital gratis"--Cover.
Keywords: Farm life -- Juvenile literature; Farms -- Juvenile literature; Agriculture -- Juvenile literature